Overview of Fall Risk and Pain Levels in Elderly Patients with Knee Osteoarthritis in General Hospital - Avriza Byan Antama Putri; Edy Soesanto; Mohammad Fatkhul Mubin; Ernawati Ernawati (Media Keperawatan Indonesia)
Knee osteoarthritis is a degenerative disease that is often experienced by the elderly, causing pain and increasing the risk of falls, which has a significant impact on quality of life. This study aims to describe the risk of falls and pain levels in elderly people with knee osteoarthritis in general hospitals. This research uses a descriptive design with a cross sectional approach. Data collection was carried out by studying medical records and interviews from 150 elderly patients suffering from knee osteoarthritis. The risk of falling was measured using the Morse Falls Scale, while the level of pain was measured using the Numeric Rating Scale. The results showed that 49.3% of patients had a low risk of falling and 56.7% experienced mild pain. The majority of patients were aged 71-90 years, with 78.7% of them being women. This study shows that the majority of elderly patients with knee osteoarthritis have a low risk of falls and mild to moderate levels of pain, with age and gender playing an important role in the prevalence of this condition.